Childhood trauma are not associated with the intensity of transient cocaine induced psychotic symptoms. Issue 3 (30th August 2015) - Karsinti, Emily; Jarroir, Marine; Zerdazi, El-Hadi; Bloch, Vanessa; Dupuy, Gaël; Belforte, Beatriz; Coeuru, Philippe; Plat, Arnaud; Deschenau, Alice; Cottencin, Olivier; Gay, Aurelia; Lack, Philippe; et al.
Abstract: A personal history of childhood trauma has been associated with the severity of psychotic symptoms in several disorders. We evaluated retrospectively cocaine-induced psychotic symptoms with the SAPS-CIP and childhood trauma with the CTQ in a clinical sample of 144 cocaine users. The SAPS-CIP score was not statistically associated with the presence or number or intensity of trauma, but was associated with rapid routes of administration (intravenous and smoked) and with frequent cocaine use. Highlights: Assessment performed with standardized questionnaires. Childhood trauma were found in 62% of the subjects. Transient cocaine-induced psychotic symptoms (TCIPS) in 88% of the subjects. No association was found between childhood trauma and TCIPS. Early age at onset of cannabis use was associated with childhood trauma.